Enoxaparin 20 mg for thromboprophylaxis in severe renal impairment - Karaoui, Lamis R. (2019)
Objective This study was performed to evaluate the efficacy of daily subcutaneous enoxaparin 20 mg in patients with renal failure. Methods This retrospective cohort study included nonsurgical patients aged ≥18 years with a creatinine clearance rate of <30 mL/minute who were prescribed enoxaparin 20 mg subcutaneously (SC) daily for ≥3 days. The main outcome measures were the occurrence of a venous thromboembolic event (VTE) and bleeding events. Results One hundred sixty patients were identified. VTE occurred in 9 patients (5.6%), and bleeding events occurred in 37 (23.1%). Multivariable analysis showed that an age of >75 years was significantly associated with an increased risk of bleeding, while a creatinine clearance rate of 15 to 29 mL/minute was significantly associated with a lower risk of bleeding. Conclusion In patients with renal failure, enoxaparin 20 mg SC daily resulted in a 5.6% incidence of VTE, which is similar to the previously published acceptable incidence of VTE in patients with normal renal function receiving enoxaparin 40 mg SC daily. The incidence of major bleeding events was 10%, which is lower than that previously published in the literature.